FACTORS OF HUMAN CAPITAL DEVELOPMENT IN THE ARCTIC - N. Silin, Anatoly; L. Belonozhko, Marina; M. Oveian, Myasnik (Revista Gênero e Interdisciplinaridade, 2020)
The relevance of the problem under study is conditioned upon the fact that at present, human capital constitutes the main factor in improving the socio-economic situation of the Arctic, ensuring the national security of the country, therefore it is very important to develop it. The problem of accumulation and use of human capital in the Arctic is caused by an insufficiently effective partnership of civil society entities, business and government, a low level of education of labour resources, competitiveness, and a low standard of living. The purpose of the paper is to develop recommendations for the development of human capital in the Arctic. The leading methods of researching the problematics of the paper include the analysis of theoretical sources, analysis of statistics, and comparison. Analysis of statistical indicators plays a crucial role in the study, since data on the development of human capital in the Arctic can be directly obtained from statistical databases. The article considers the essence of human capital, the identification of its components, the factors of its development, development issues, analyses the development of human capital in the Arctic, identifies the problems of human capital development in the Arctic, and develops ways to solve them. The materials of the paper are of practical value for the development of human capital in the Arctic or other regions of the country.